PENGARUH JUMLAH UANG BEREDAR, VELOCITY OF MONEY, DAN PRODUK DOMESTIK BRUTO TERHADAP INFLASI DI INDONESIA TAHUN 1997.Q1 – 2019.Q4 - Muhammad, Noor Pratama Fahny; Rosyetti, Rosyetti; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This This study aims to analyze the effect of the money supply, velocity of money and gross domestic product on inflation in Indonesia in the long and short term 1997.Q1 - 2019.Q4. This research was conducted in Indonesia by examining the effect of the money supply, velocity of money and gross domestic product on the inflation rate in Indonesia in 1997.Q1 - 2019.Q4. The purpose of using data from the 1997.Q1 - 2019.Q4 period is to produce accurate estimates and conclusions about the variables studied and to be able to find out the interpretation of the research object using quarterly data for 22 years. The method used in this research is descriptive and quantitative methods. The analysis model used is multiple linear regression analysis (assisted by EViews 10 software). The data analysis technique used is the error correction model. As for seeing the effect of the independent variable on the dependent variable in the long and short term, the final result will measure the effect of the money supply, velocity of money and gross domestic product on inflation in Indonesia in the long and short term. The results of this study indicate that in the long run, the money supply and velocity of money have a positive and significant effect on inflation and gross domestic product has a negative and significant effect on inflation. Meanwhile, in the short term velocity of money has a positive and significant effect and gross domestic product has a negative and significant effect and the money supply has no effect on inflation.Keywords: inflation, money supply, velocity of money, gross domestic product